Different modes of full-thickness macular hole formation. (January 2021) - Bringmann, Andreas; Unterlauft, Jan Darius; Barth, Thomas; Wiedemann, Renate; Rehak, Matus; Wiedemann, Peter
Abstract: Full-thickness macular holes (FTMH) are an important cause of visual deterioration. However, different modes of FTMH formation are less investigated. It is also not clear whether the development of edematous cysts contributes to FTMH formation. In this retrospective case series of 30 eyes of 30 patients, we describe using spectral-domain optical coherence tomography different modes of FTMH formation. Morphological alterations of established FTMH are shown in 5 eyes of 5 patients. We found in 2 of 30 eyes investigated that anterior hyaloidal traction induced a hyperreflectivity of the inner Müller cell layer of the foveola prior to FTMH formation. In 3 eyes, FTMH were caused by anterior hyaloidal traction which produced foveal pseudocysts that developed to an outer lamellar hole (OLH) characterized by a disruption of the central outer retina. The OLH developed to a FTMH by the disruption of the inner layer of the foveola. FTMH formation from an OLH by hyaloidal traction was observed also in further 7 eyes. In 2 eyes, the OLH, which preceded FTMH formation, was generated by a serous retinal detachment. In 3 eyes, anterior hyaloidal traction caused a detachment of the fovea from the retinal pigment epithelium (RPE); the subsequent disruption of the foveola resulted in a FTMH. Six eyes showed the development of a FTMH from a degenerative lamellar hole (DLH). In 5 eyes with macular pucker, FTMH were formed by traction of epiretinal membranes (ERM) or hyaloidal traction. Two eyes showed the development of a FTMH by anterior or tangential hyaloidal traction likely without a formation of an OLH. FTMH formation from an OLH proceeded with or without an enlargement of cystic cavities in the foveal walls. The formation of FTMH from a DLH, after a detachment of the fovea, and in macular pucker eyes was associated with a formation of cystic cavities in the foveal walls. The best-corrected visual acuity (BCVA) of eyes with an OLH or FTMH was inversely correlated to the base and minimum diameters of the holes, and with the height of the foveal walls; the highest correlation coefficients were found between the BCVA and the base diameter. The data show that FTMH may be formed via different modes by hyaloidal traction and/or traction of ERM, or after a serous retinal detachment. It is suggested that, after FTMH formation, the impaired fluid clearance through the RPE after detachment of the central outer retina causes the development of edematous cysts in the foveal walls which enlarges the FTMH. The BCVA of eyes with an OLH or FTMH mainly depends on the size of the central photoreceptor-free area. Highlights: Full-thickness macular holes (FTMH) a major cause of vision loss. Many cases of FTMH are produced from an outer lamellar hole (OLH). FTMH are also formed from degenerative lamellar holes and in macular pucker eyes. FTMH formation from OLH proceeds with or without the formation of edematous cysts. Visual acuity of eyes with OLH or FTMH is best correlated to the base hole diameter.